Identification and functional characterization of a novel susceptibility locus for small vessel vasculitis with MPO-ANCA. (9th December 2021) - Dahlqvist, Johanna; Ekman, Diana; Sennblad, Bengt; Kozyrev, Sergey V; Nordin, Jessika; Karlsson, Åsa; Meadows, Jennifer R S; Hellbacher, Erik; Rantapää-Dahlqvist, Solbritt; Berglin, Ewa; Stegmayr, Bernd; Baslund, Bo; et al.
Abstract: Objective: To identify and characterize genetic loci associated with the risk of developing ANCA-associated vasculitides (AAV). Methods: Genetic association analyses were performed after Illumina sequencing of 1853 genes and subsequent replication with genotyping of selected single nucleotide polymorphisms in a total cohort of 1110 Scandinavian cases with granulomatosis with polyangiitis or microscopic polyangiitis, and 1589 controls. A novel AAV-associated single nucleotide polymorphism was analysed for allele-specific effects on gene expression using luciferase reporter assay. Results: PR3-ANCA + AAV was significantly associated with two independent loci in the HLA-DPB1/HLA-DPA1 region [rs1042335, P  = 6.3 × 10 −61, odds ratio (OR) 0.10; rs9277341, P  = 1.5 × 10 −44, OR 0.22] and with rs28929474 in the SERPINA1 gene ( P  = 2.7 × 10 −10, OR 2.9). MPO-ANCA + AAV was significantly associated with the HLA-DQB1/HLA-DQA2 locus (rs9274619, P  = 5.4 × 10 −25, OR 3.7) and with a rare variant in the BACH2 gene (rs78275221, P  = 7.9 × 10 −7, OR 3.0), the latter a novel susceptibility locus for MPO-ANCA + granulomatosis with polyangiitis/microscopic polyangiitis. The rs78275221-A risk allele reduced luciferase gene expression in endothelial cells, specifically, as compared with the non-risk allele. Conclusion: We identified a novel susceptibility locus for MPO-ANCA + AAV and propose that the associated variant is of mechanistic importance, exerting a regulatory function on gene expression in specific cell types.